2011
DOI: 10.1096/fj.11-184036
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of NDM‐1 reveals a common β‐lactam hydrolysis mechanism

Abstract: Metallo-β-lactamases (MBLs) hydrolyze most β-lactam antibiotics, and bacteria containing this kind of enzyme pose a serious threat to the public health. The newly identified New Delhi MBL (NDM-1) is a new member of this family that shows tight binding to penicillin and cephalosporins. The rapid dissemination of NDM-1 in clinically relevant bacteria has become a global concern. However, no clinically useful inhibitors against MBLs exist, partly due to the lack of knowledge about the catalysis mechanism of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
352
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(382 citation statements)
references
References 50 publications
29
352
1
Order By: Relevance
“…At this point it may be necessary to briefly discuss the connection between the tighter and weaker metal ion binding sites (characterised by K d1 and K d2 ) and the two available binding sites in the catalytic centre, labelled Zn1 and Zn2 (Figure 4). In B1-and B3-type MBLs Zn1 is likely to be associated with K d1 , supported, for instance, by crystallographic data that indicate a higher metal ion occupancy for this site than Zn2 [35] [36] [46] [59] [64]. An exception appears to be the B3-type MBL GOB from Elizabethkingia meningoseptica, where H116 in the Zn1 position (Figure 4) is replaced by a glutamine; a combination of kinetic and spectroscopic data indicate that this enzyme operates in mononuclear form with the metal ion bound to Zn2 (i.e.…”
Section: Interactions Between Mbls and Metal Ionsmentioning
confidence: 88%
“…At this point it may be necessary to briefly discuss the connection between the tighter and weaker metal ion binding sites (characterised by K d1 and K d2 ) and the two available binding sites in the catalytic centre, labelled Zn1 and Zn2 (Figure 4). In B1-and B3-type MBLs Zn1 is likely to be associated with K d1 , supported, for instance, by crystallographic data that indicate a higher metal ion occupancy for this site than Zn2 [35] [36] [46] [59] [64]. An exception appears to be the B3-type MBL GOB from Elizabethkingia meningoseptica, where H116 in the Zn1 position (Figure 4) is replaced by a glutamine; a combination of kinetic and spectroscopic data indicate that this enzyme operates in mononuclear form with the metal ion bound to Zn2 (i.e.…”
Section: Interactions Between Mbls and Metal Ionsmentioning
confidence: 88%
“…These hydrogen bonds and interactions are absent in VIM-7 and VIM-4 due to the presence of histidine at this position (16,20). Residue 224 is a conserved lysine in many B1 family MBLs and was found to be critical for binding the carboxyl group on the C-3/C-4 atom of the substrate (21,32,33). Here we created a H224Y mutant to investigate the role of residue 224 in the structure, enzymatic activity, and thermostability of VIM-7 and the importance of potential additional hydrogen bonds.…”
mentioning
confidence: 99%
“…It is not yet known which position(s) plays a critical role in the enzymatic activities. The crystal structure of NDM-1 revealed that the active site of NDM-1 is located at the bottom of a shallow groove enclosed by 2 important loops, L3 and L10 (21,22,23,24). Residues 88 and 130, however, were not lo- cated in these loops.…”
mentioning
confidence: 99%